A Sustainability Reporting Framework For Villages Based on The Global Reporting Initiative (GRI): A Case Study of Tulungrejo Village - Fariz Yusuf Rafi; Eko Ganis Sukoharsono (PT. Maju Malaqbi Makkarana, 2026)
This study aims to develop and implement a sustainability reporting framework for Tulungrejo Village based on the Global Reporting Initiative (GRI) standards. Unlike evaluative studies, this research focuses on designing a village sustainability report that had not previously been available. The research process involved identifying sustainability issues, engaging stakeholders, and conducting a materiality analysis in accordance with GRI 3 to determine relevant topics. The selected material topics were then mapped into GRI 200 (economic), 300 (environmental), and 400 (social) standards, and compiled using the “with reference” approach. The findings indicate that village sustainability reporting can be implemented adaptively by selecting indicators that align with the village’s characteristics and capacity. This study proposes a GRI-based sustainability reporting framework that can serve as a practical guideline for village governments to enhance transparency and accountability in resource management.